An evaluation of the Federal Reserve estimates of the natural rate of unemployment in real time - Fabià Gumbau-Brisa; Giovanni P. Olivei (Federal Reserve Bank of Boston, 2013)
The authors derive an estimate of the Federal Reserve's assessment of the natural rate of unemployment in real time from the Greenbook forecast of inflation. The estimated natural rate starts to rise noticeably in the second half of the mid-1970s. It stays relatively high in the 1980s, and then declines noticeably in the second half of the 1990s. They compare the Greenbook estimates with the estimates obtained in real time from simple relationships that extract information about the natural rate of unemployment from the dynamics of inflation, aggregate demand, and the functioning of the labor market. When differences between these measures and the Greenbook arise, the improvement to the Greenbook inflation forecast that would have been achieved by using a different estimate of the natural rate of unemployment is typically small.
Keywords: E37; E47; E5; 330